Leaving the lost “village” confronting today’s Rome (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
The potential to be recovered is many. It is not by establishing the MAXXI, and perhaps by exporting it to L’Aquila (the last one found), that the problems are solved, when the Macro has already been doubled and when the Palazzo delle Esposizioni, which is practically empty, has existed for decades. The Quirinale stables offer exhibitions that are often essentially tourist packages, not much more. There is a need to offer spaces for artistic innovations.